2017
DOI: 10.1186/s12864-017-4175-7
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing, calcium signaling, and other novel pathways are associated with the formation of butterfly eyespots

Abstract: BackgroundOne hypothesis surrounding the origin of novel traits is that they originate from the co-option of pre-existing genes or larger gene regulatory networks into novel developmental contexts. Insights into a trait’s evolutionary origins can, thus, be gained via identification of the genes underlying trait development, and exploring whether those genes also function in other developmental contexts. Here we investigate the set of genes associated with the development of eyespot color patterns, a trait that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 113 publications
(119 reference statements)
3
57
0
Order By: Relevance
“…Transcriptome analyses revealed that a surprisingly large number of genes were specifically regulated in the area of pigmentation formation: 78 genes were upregulated commonly in the pigmentation area and by wingless, and 73 genes were downregulated commonly in the pigmentation area and by wingless. In the butterfly Bicyclus anynana, 132 genes were upregulated and 54 genes were downregulated in relation to eye spot formation [24]. In comparison with these numbers of genes in butterflies, the number of genes identified by our results seem reasonable.…”
Section: A Large Number Of Genes Were Specifically Regulated In the Asupporting
confidence: 53%
See 1 more Smart Citation
“…Transcriptome analyses revealed that a surprisingly large number of genes were specifically regulated in the area of pigmentation formation: 78 genes were upregulated commonly in the pigmentation area and by wingless, and 73 genes were downregulated commonly in the pigmentation area and by wingless. In the butterfly Bicyclus anynana, 132 genes were upregulated and 54 genes were downregulated in relation to eye spot formation [24]. In comparison with these numbers of genes in butterflies, the number of genes identified by our results seem reasonable.…”
Section: A Large Number Of Genes Were Specifically Regulated In the Asupporting
confidence: 53%
“…There is an ongoing discussion about whether a large gene circuit is recruited or many genes are individually recruited to form a circuit during the evolution of a novel trait [41,42]. Examples of co-option of pre-existing circuits consisting of multiple regulatory genes are known from animals and plants [11,24,[43][44][45][46]. In the present case, we can ask whether the large gene network for pigmentation regulated by a master control gene, wingless, was co-opted all at the same time, or whether individual genes were co-opted one by one to form the current network.…”
Section: Evolutionary Scenario Of Pigmentation Pattern Evolutionmentioning
confidence: 99%
“…Among our identified candidates, we observed a total of seven genes previously implicated in eyespot development in B. anynana : CDase, Dpp, Antp, Ubx, Sal3, Cd63 , and Syntaxin 7 (Brunetti et al 2001; Tong et al 2014; Özsu and Monteiro 2017; Connahs et al 2019) (Table 2). From these, only dpp and Cd63 remained associated at the highest significant threshold of 7 SD.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes are within or near the area of strongest association, and only Cd63 has an associated SNP within an intron (Table 3 and Figure 4). Neutral Ceramidase ( CDase ; BANY.1.2.g00030) is an enzyme involved in the metabolism of sphingolipids which is down-regulated in eyespots relative to flanking wing tissue (Özsu and Monteiro 2017). Sphingolipids appear to function in a variety of cell signaling pathways but are still poorly understood (Hannun and Obeid 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular calcium waves transmit local information from the initiator cell to a large number of cells in order to coordinate and synchronize their activity during development (Moreno-Juan et al, 2017;Akahoshi , Hotta and Oka 2017, Wallingford et al 2001, Webb and Miller 2003, Özsu and Monteiro 2017. Surprisingly, endogenous calcium waves during embryogenesis of insects have not been documented.…”
Section: Introductionmentioning
confidence: 99%